Canadian Labour Relations Under the Charter: Exploring the Implications - Carter, Donald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
Can legal tools used by judges and lawyers adequately deal with the public policy issues that underly any alteration of our present system of industrial relations.